2022
DOI: 10.1038/s41598-022-09741-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of the sofosbuvir/velpatasvir combination for the treatment of patients with early mild to moderate COVID-19

Abstract: SARS-CoV-2 is still a health problem worldwide despite the availability of vaccines. Therefore, there is a need for effective and safe antiviral. SARS-CoV-2 and HCV necessitate RNA-dependent RNA polymerase (RdRp) for replication; therefore, it has been hypothesized that RdRp inhibitors used to treat HCV may be effective treating SARS-CoV-2. Accordingly, we evaluated the effect of the sofosbuvir/velpatasvir (SOF/VEL) combination in early SARS-CoV-2 infection. A multicenter case–control study was conducted, enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Exonuclease proofreader inhibitors would be highly desirable in the clinic for potential combination treatment with nucleotide analogs and could improve efficacy, prevent the development of resistance and allow the addition of more therapeutic options as vaccine protection begins to wane. Indeed, encouraging clinical data has recently been reported for Epclusa® in mild to moderate COVID-19 56 . Hepatitis C NS5A therapeutics Epclusa® (velpatasvir/sofosbuvir) and Zepatier® (elbasvir/grazoprevir) would be excellent starting points for optimization of potency and pharmacokinetic properties to enable clinical evaluation in COVID-19 patients in combination with remdesivir.…”
Section: Discussionmentioning
confidence: 98%
“…Exonuclease proofreader inhibitors would be highly desirable in the clinic for potential combination treatment with nucleotide analogs and could improve efficacy, prevent the development of resistance and allow the addition of more therapeutic options as vaccine protection begins to wane. Indeed, encouraging clinical data has recently been reported for Epclusa® in mild to moderate COVID-19 56 . Hepatitis C NS5A therapeutics Epclusa® (velpatasvir/sofosbuvir) and Zepatier® (elbasvir/grazoprevir) would be excellent starting points for optimization of potency and pharmacokinetic properties to enable clinical evaluation in COVID-19 patients in combination with remdesivir.…”
Section: Discussionmentioning
confidence: 98%
“…A study conducted by Messina V et al enrolled 120 patients with COVID-19 infection; total of 30 patients were offered treatment with Sofosbuvir and Velpatasvir, and out of those who were treated with the above-mentioned medications, 60% had both infections Covid-19 and HCV and this study also stressed that Sofosbuvir and Velpatasvir when used in earlier phase of infection which can be an excellent help for hastening the spread of this deadly virus, hospitalization and stopping the disease progression (Messina et al, 2022). In contrast, our study also enrolled 100 patients and treated them with Sofosbuvir and Velpatasvir, revealing the same results as mentioned in the study conducted in Italy by Messina V et al (Messina et al, 2022), which is highly comparable with our investigation. A study conducted by Sayad B at Farabi Hospital in Kermanshah Province, Iran.…”
Section: Discussionmentioning
confidence: 67%
“… 24 Other emerging evidence from a case–control study suggested that early treatment of mild to moderate COVID-19 with sofosbuvir/velpatasvir, also used for the treatment of hepatitis C, may promote faster viral elimination and prevent disease progression. 31 The randomized, placebo-controlled DISCOVER trial, however, showed no benefits of sofosbuvir/daclatasvir in patients hospitalized for COVID-19. 32 Nitazoxanide has shown a range of results when used for treatment and prevention in other trials.…”
Section: Discussionmentioning
confidence: 99%